PRESENT CONDITION OF BORON SUPPLY IN SOILS OF POLTAVA REGION - Коваль, В. В.; Наталочка, В. О.; Ткаченко, С. К.; Міненко, О. В. (Scientific Progress & Innovations, 2013)
The publication presents the results of long-term studies and summarizes the current condition of soil fertility of agricultural land in Poltava Region. The dynamics of providing soils of the Poltava area with the boron is analyzed and the recommendations in relation to their further stopping degradation and to renewal is given. During 2001–2010 laboratory researches detected, that content of the boron in soils of area for two last rounds of inspection did not change. According to the information of the VIII round of inspection, the average content of the boron is made by 1,05 mgs/kg of soil, against a 1,11 mg/kg in the IX round.